Serum trans fatty acids, asymmetric dimethylarginine and risk of acute myocardial infarction and mortality in patients with suspected coronary heart disease: a prospective cohort study. Issue 1 (December 2016) - Borgeraas, Heidi; Hertel, Jens; Seifert, Reinhard; Berge, Rolf; Bohov, Pavol; Ueland, Per; Nygård, Ottar; Hjelmesæth, Jøran
Abstract Background Trans fatty acids (TFAs) have been found to impair flow mediated vasodilation and nitric oxide (NO) production. We sought to examine if serum TFA levels are associated with plasma levels of the NO inhibitor asymmetric dimethylarginine (ADMA) and if possible relationships between serum TFA and cardiovascular morbidity or mortality are mediated or modified by plasma ADMA levels. Methods The cohort included patients who underwent coronary angiography for suspected coronary heart disease in 2000–2001. Serumtrans 16:1n7 andtrans 18:1 isomers were determined by gas liquid chromatography and the summation of these two TFAs is reported as TFA (percentage by weight (wt%) or concentration). Associations between TFAs and ADMA were estimated by calculating the Spearman's rank correlation coefficient (ρ), and risk associations with AMI, cardiovascular death and all-cause mortality across quartiles of TFAs (wt% or concentration) were explored by Cox modeling. Results A total of 1364 patients (75 % men) with median (25th, 75th percentile) age 61 (54, 69) years, serum TFA 0.46 (0.36, 0.56) wt% and plasma ADMA 0.59 (0.50, 0.70) μmol/L were studied. Serum TFA levels (ρ = 0.21, p  < 0.001), trans 16:1n7 (ρ = 0.22, p  < 0.001) andtrans 18:1 (ρ = 0.20, p  < 0.001) levels were significantly correlated with plasma ADMA levels. During the median (25th, 75th percentile) follow-up time of 5.8 (4.5, 6.4) years, 129 (9.5 %) patients experienced an AMI, 124 (9.1 %) died, whereof 66 (53 %) due to cardiovascular causes. After multivariate adjustments no significant associations between serum TFA levels (wt% or concentration) and incident AMI, CV death and all-cause mortality were observed. Similar results were obtained when repeating the analyses withtrans 16:1n7 andtrans 18:1 individually. Plasma ADMA levels did not significantly modify the associations between TFA levels and outcomes. Conclusions Serum TFA levels were positively correlated with plasma ADMA levels. After multivariate adjustments, TFAs were not associated with incident AMI or mortality, and associations were not influenced by ADMA. Trial registration Clinicaltrials.gov Identifier:NCT00354081